Exploring the Locus of Invention: The Dynamics of Network Communities and Firms' Invention Productivity - Sytch, Maxim; Tatarynowicz, Adam (Academy of Management Journal, 2014)
Departing from prior research analyzing the implications of social structure for actors' outcomes by applying either an ego network or a global network perspective, this study examines the implications of network communities for the invention productivity of firms. Network communities represent dense and nonoverlapping structural groups of actors in a social system. A network community lens helps identify new ways to study firms' access to diverse knowledge inputs in a dynamic system of interorganizational relationships. Specifically, we examine how the membership dynamics of a network community affect the invention productivity of member firms by either enabling or constraining access to broad, diverse knowledge inputs. Our findings suggest, first, that a firm reaps the greatest invention benefits in a network community with moderate levels of membership turnover. Second, a firm attains the greatest invention productivity when its own rate of movement across different network communities is moderate. Third, we find that community members located in the core of their network community can benefit more from membership dynamics and prior community affiliations than those on its periphery. In empirical analyses, we use the evolving community structure of the network of interorganizational partnerships in the global computer industry over 1981–2001 to predict firms' patenting rates.